Penerapan Metode Full Costing dalam Menetapkan Harga Jual UMKM Latopia Kota Tegal - Sarno .; Aina Salsabila (CV.ITTC INDONESIA, 2026)
UMKM Latopia Keysha in Tegal City, which produces 13 variants of latopia, has been setting its selling prices based solely on market estimation due to limited bookkeeping. This descriptive quantitative research with a case study approach aims to calculate the Cost of Goods Manufactured (COGM) using the full costing method through a joint cost approach, formulate selling prices via cost-plus pricing, and prepare an income statement. Data were gathered through questionnaires and literature studies. The results showed that the total joint cost reached IDR 140,380,181.00, with an accumulated COGM of IDR 221,811,909.00. Based on a target profit margin of 50%, the selling price calculation per unit yielded the highest amount for the chocolate-cashew variant (IDR 3,620.00) and the lowest for the fruit variant (IDR 2,007.00). Throughout the June–July 2025 period, the business successfully recorded a real net profit of IDR 141,756,591.00, reflecting a profitability rate of 38.91%. The implementation of this calculation helps the business owner transition from guesswork to data-driven business decisions.